Transport Properties in Electrodes for Lithium-Ion Batteries: Comparison of Compact versus Porous NCM Particles. Issue 10 (1st October 2022) - Schneider, Luca; Klemens, Julian; Herbst, Eike Christian; Müller, Marcus; Scharfer, Philip; Schabel, Wilhelm; Bauer, Werner; Ehrenberg, Helmut
Abstract : Previous investigations on porous Li(Nix Coy Mnz )O2 (NCM) particles with shortened diffusion paths and an enlarged interface between active material and electrolyte show improved rate capability and cycle stability compared to compact particles. Due to the additional intragranular porosity of the active material, also the pore structure of the overall electrode, and as consequence, the ionic transport in the pore phase is altered. In addition, the particle morphology influences the ohmic contact resistance between the current collector and electrode film. These effects are investigated using impedance spectroscopy in symmetrical cells under blocking conditions. The ionic resistance and the tortuosity of the electrodes are determined and analyzed by a transmission line model. Tortuosity is higher for porous particles and increases more during calendering. This limits the options to densify these electrodes to the same level as with compact particles. In a further approach, the method is used to explain the drying related performance differences of these electrodes. At higher drying rates, the contact and the ionic resistance of electrodes with compact particles increases more strongly as for electrodes with porous particles. These investigations provide new insights into the ion transport behavior and enable a better understanding of the impact of the electrode processing condition.